2000
DOI: 10.1614/0043-1745(2000)048[0487:brmirb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Between-row mowing + in-row band-applied herbicide for weed control inGlycine max

Abstract: Most farmers now rely on herbicides and, to a lesser extent, cultivation to control weeds in Glycine max in the Midwest. However, the general public is concerned that widely used herbicides will contaminate surface and groundwater. Alternative ways to control weeds in field crops are needed to reduce or prevent herbicide contamination of surface and groundwater. A new between-row-mowing weed management system that consists of band-applied herbicides over crop rows + two or more between-row mowings was tested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 26 publications
1
23
0
2
Order By: Relevance
“…In earlier research (Donald 2000a(Donald , 2000b(Donald , 2005Donald et al 2001) and in these experiments (Figures 3 to 5), most summer annual total weed cover escaping between-row mowing treatments was giant foxtail. Mowing controlled annual broadleaf and grass weeds differently.…”
Section: Total Weed Cover and Maximum Weed Canopy Heightmentioning
confidence: 52%
See 1 more Smart Citation
“…In earlier research (Donald 2000a(Donald , 2000b(Donald , 2005Donald et al 2001) and in these experiments (Figures 3 to 5), most summer annual total weed cover escaping between-row mowing treatments was giant foxtail. Mowing controlled annual broadleaf and grass weeds differently.…”
Section: Total Weed Cover and Maximum Weed Canopy Heightmentioning
confidence: 52%
“…Giant foxtail cover became greater, faster, when corn shading was reduced by decreased or delayed crop canopy closure due to reduced stands. In previous research in reduced-and no-till (Donald 2000a(Donald , 2000bDonald et al 2001), a second between-row mowing killed the growth of giant foxtail surviving the first mowing. Corn shading likely limited subsequent giant foxtail germination, emergence, and recovery from mowing (Santelmann et al 1963).…”
Section: Total Weed Cover and Maximum Weed Canopy Heightmentioning
confidence: 86%
“…Integration of interrow cultivation with banding of herbicide full rate over the crop rows did not ensure weed control and did not provide satisfactory bean yield in both years, as expected, although Buhler et al (1992) and Donald (2000) demonstrated satisfactory weed control by band herbicide application over soybean rows combined with mechanical interrow cultivation. …”
Section: Weed Managementmentioning
confidence: 67%
“…When mowed close to the soil surface two or more times, populations of S. faberi were eliminated or suppressed in Missouri soybean and corn fields (Donald 2000a(Donald , b, 2006Donald et al 2001). Shading by the crop canopy also reduced weed growth in these studies.…”
Section: Response To Other Human Manipulationsmentioning
confidence: 79%